Exploring Moral Values in Al-Minah Al-Saniyah for Modern Islamic Education: Kajian Nilai-Nilai Akhlak dalam Al-Minah Al-Saniyah untuk Pendidikan Islam Modern - Achmad Syamsul; Budi Haryanto (Academia Open, 2023)
This study explores the moral values in Al-Minah Al-Saniyah by ‘Abd Al-Wahab Al-Sya’rani, addressing concerns about declining morals, especially among students. General Background: The decline in moral behavior requires renewed attention to Islamic texts that emphasize moral education. Specific Background: Modern moral practices are increasingly deviating from religious teachings, prompting a need to revisit classical works. Knowledge Gap: The relevance of Al-Minah Al-Saniyah in today’s Islamic education remains under-explored. Aims: The study investigates the moral teachings in the book and their applicability to the Aqidah Akhlak curriculum in Madrasah Aliyah. Results: The text highlights key values like repentance and sincerity, which are essential for moral education. Novelty: This study shows how the book can be integrated into the modern curriculum, offering fresh insights into moral instruction. Implications: It advocates using classical Islamic texts to address contemporary moral challenges in education. Highlights: Al-Minah Al-Saniyah emphasizes core moral values like repentance, honesty, and sincerity. The book can be integrated into modern curricula to enhance Aqidah Akhlak instruction. Classical Islamic texts offer valuable insights to address contemporary moral challenges. Keywords: Moral Education, Islamic Pedagogy, Aqidah Akhlak, Madrasah Aliyah